Isolation and Characterization of Dryland Microfungi From Northern Insana as Potential Sources of Antibacterial Agents - mere, janrigo klaumegio; Edi, Eduardus; Nomi, Anastasia Grandivoriana (Jurnal Kimia Fullerene, 2025)
Microfungi are one of the most extensively studied groups of microorganisms due to their remarkable ability to produce a diverse range of unique bioactive compounds. This study aimed to explore and characterize microfungi isolated from the drylands of North Insana as potential sources of sustainable antibacterial agents. The research methods included the isolation of microfungi, morphological identification, and evaluation of antibacterial activity using the disc diffusion method. Based on morphological characterization, microfungi isolated from the North Insana dry soil showed similarities to three genera, namely Mucor, Penicillium/Aspergillus, and Aspergillus. Antibacterial assays revealed that all three isolates exhibited varying degrees of activity, ranging from moderate to strong, against Staphylococcus aureus. Isolate 1 produced an inhibition zone of 7.6 ± 0.20 mm (moderate activity), isolate 2 produced 10.17 ± 0.06 mm (strong activity), and isolate 3 produced 10.77 ± 0.06 mm (strong activity). According to the Tukey test (p < 0.05), isolate 3 showed no significant difference from the standard antibiotic chloramphenicol (11.23 ± 0.15 mm), indicating a comparable antibacterial effectiveness. These results suggest that dryland-endemic microfungi possess adaptive biosynthetic capacities, enabling them to produce antibacterial secondary metabolites in response to extreme environmental stress. This potential reinforces the role of dryland microfungi as promising new sources of natural antibacterial compounds for sustainable biotechnological and health applications